Design and discovery of thioether and nicotinamide containing sorafenib analogues as multikinase inhibitors targeting B-Raf, B-RafV600E and VEGFR-2. Issue 9 (15th May 2018) - Sun, Shaofeng; He, Zuopeng; Huang, Mindong; Wang, Ningning; He, Zongzhong; Kong, Xiangkai; Yao, Jianwen
Graphical abstract: Thioether and nicotinamide-containing sorafenib analogues with better anti-proliferative and anti-angiogenic activities than sorafenib were well designed and synthesized as B-Raf, B-Raf V600E and VEGFR-2 multikinase inhibitors. Abstract: New sorafenib derivatives containing thioether and nicotinamide moiety were designed and synthesized as B-Raf, B-Raf V600E and VEGFR-2 multikinase inhibitors. Their in vitro enzymatic inhibitory activities against B-Raf, B-Raf V600E and VEGFR-2 and their antiproliferative activities against HCT-116 and B16BL6 cell lines were evaluated and described. Most of the compounds showed potent activities against both cell lines and specific kinases. Compoundsa1, b1 andc4, which exhibited the most potent inhibitory activities against B-Raf with IC50 of 21 nM, 27 nM and 17 nM, B-Raf V600E with IC50 of 29 nM, 28 nM and 16 nM, VEGFR-2 with IC50 of 84 nM, 46 nM and 63 nM, respectively, and good antiproliferative activities, also demonstrated competitive antiangiogenic activities to sorafenib in in vitro HUVEC tube formation assay.